Human growth and development. - Cameron, Noel; Schell, Lawrence M. (Academic Press, 2021)
Human Growth and Development, Third Edition provides a comprehensive volume covering the biology of human growth and the genetic, endocrine, environmental, nutritional, and socio-economic factors that contribute towards its full expression. Human Growth and Development continues to be a valuable resource for researchers, professors and graduate students across the interdisciplinary area of human development. For the new edition, updates are made to all fourteen of the "core chapters" of the book which form the essential reading for a comprehensive understanding of human growth and development. Additionally, new special topics are covered including the interpretation of recently found sub-adult fossils that expand our understanding of the evolution of human growth and a discussion of the early pattern of growth and development as the developmental origins of risk for non-communicable diseases of adulthood. Human Growth and Development, Third Edition includes contributions from the well-known experts in the field and is the most reputable, comprehensive resource available